Analisis Keamanan Arsitektur Sistem Smart Farming Berbasis NIST Cybersecurity Framework di Living Lab Universitas Widyatama - Albani Akbar; Ari Purno Wahyu Wahyu Wibowo; Ignatius Oki Dewa Brata (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of Internet of Things (IoT) technology has driven digital transformation in the agricultural sector through the concept of Smart Farming, including in the academic environment. However, increased system connectivity and automation are also accompanied by increased cybersecurity risks, especially in IoT systems that are developed independently and are closed (proprietary). This study aims to analyze the cybersecurity posture of the IoT-based Smart Farming system architecture in the Living Lab of Widyatama University using the National Institute of Standards and Technology Cybersecurity Framework (NIST CSF) version 2.0. The study uses a qualitative method with a case study approach, where the analysis focuses on the six core functions of the NIST CSF, namely Govern, Identify, Protect, Detect, Respond, and Recover. The object of the study is an off-grid Smart Farming system that utilizes Solar Power Plants (PLTS) for real-time monitoring of catfish cultivation water quality. The results of the study indicate that the level of system security maturity is still at Tier 1 (Partial), with major weaknesses in the aspects of security governance, early detection mechanisms, and incident response and recovery procedures. While the system offers advantages in energy independence and operational continuity, the absence of formal security policies and adequate technical controls potentially increases the risk of operational disruptions due to cyber threats. This study recommends implementing NIST CSF v2.0-based security to improve data integrity, operational reliability, and resilience of IoT-based Smart Farming systems in academic environments.